The Impact of Cementing Techniques on Implant Longevity in Relation to Keel Length in Persona and NexGen Knee Arthroplasty: A Comprehensive Study - Arash Sharafat Vaziri, MD; Mohammad Naghi Tahmasebi, MD; Hoseinali Hadi, MD; Sina Javidmehr, MD; Sohrab Keyhani, MD; Zahra Vahdati, MD; Hossein Nematian, MD; Yalda Farahmand, MD (Arthroplasty Today)
Background: The aim of this study was to investigate the efficacy of our modified cementing technique in reducing the rate of aseptic tibial loosening focusing on its relationship with keel length. Methods: Every participant who underwent primary total knee arthroplasty (TKA) between August 2014 and September 2022 with a minimum of 4-year follow-up using 1 of 3 implants were included: Persona + conventional cementing technique; Persona + modified cementing technique; and NexGen LPS-Flex. The modifications applied include better preparation of the bone surfaces and the cancellous bone cavities, pressurizing the cement and interstitial fluid suction at the same time, applying a layer of cement on the surfaces of the tibia and implant, and immobilizing the limb. Kaplan-Meier analyses were performed to estimate survivorship. Results: A total of 988 of 1039 primary TKAs (95.1%) were included with follow-up of 89.26 ± 7.32 months. Twenty eight (2.83%) TKA required revisions due to aseptic tibial loosening; 3 (1.1%) in the NexGen group, 21 (6.9%) in the conventionally cemented Persona group, and 4 (0.9%) within the modified cemented Persona group. Aseptic loosening occurred at a mean of 69.00 ± 2.65, 34.57 ± 22.90, and 68.50 ± 3.42, respectively. Survivorship for aseptic loosening was 98.9%, 93.1%, and 99.1% at 8 years, respectively. The revision rate for early (during the first 24 months) aseptic loosening was 4.6% in the conventionally cemented Persona group. No early aseptic loosening reported in other 2 groups. Conclusions: In conclusion, meticulous cementing techniques can reduce the rate of tibial loosening in shorter keel designs.